Implementasi Sistem Kendali Otomatis Pada Industri Manufaktur: Kajian Literatur - Kurniawan, Mohammad Simar Kurniawan; Wijaya, Kahfi; Hardi Purba, Humiras (Faculty of Industrial Technology Universitas Islam Indonesia, 2025)
The implementation of automatic control systems has become a crucial element in the development of modern industries and smart home technologies. These systems, comprising sensors, controllers, and actuators, enable more efficient operations, reduce human errors, and increase productivity. In the era of Industry 4.0, the application of automatic control has expanded from manufacturing to various aspects of daily life, such as smart homes that can automatically regulate temperature and lighting. Various control techniques, such as PID, fuzzy, and model predictive control, have been developed to meet the specific needs of different industries. This literature review aims to provide comprehensive insights into the basic concepts, techniques, and methods used in automatic control systems, as well as to identify existing challenges and opportunities. Through a systematic review of 35 relevant articles, this study reveals various practical applications and benefits of automatic control systems and suggests broader and more effective adoption of this technology to enhance quality and efficiency across various sectors.